Kind of cursed eaudiobook - Fournet, Stephanie (Tantor Media, 2020)
Every woman in Millie Delacroix's family is cursed—kind of. Birth control just doesn't work for them. Like ever. Going to the altar knocked up is pretty much a family tradition. And twenty-four-year-old Millie refuses to let that happen to her—again. Especially now that she's responsible for raising her brothers and sister. A life of celibacy is her best defense—at least until the kids are grown and can take care of themselves. And, really, what's ten years with no sex? No men. No sex. No love. It's a fool-proof plan. Until she meets Luc Valencia. The Mexican-American contractor is just trying to do his best. Since his father handed him the reins to the family business, every day is a test to prove himself. At this point in his life, professionalism has to be his top priority. At least until Millie becomes Luc's client. Even with too much on her shoulders, the feisty redhead has the power to set him off, crack him up, or bring him to his knees. All he has to do is resist falling for her through one kitchen remodel, and everything will be fine. Right?